PEMBUATAN SEDIAAN TEH CELUP DAUN SAGA (Abrus precatorius Linn) DAN DAUN SIRIH (Piper betle ) UNTUK OBAT KUMUR - Puspita, Sri; Yanto, Elih Sutisna; Farhan, Farhan (Sekolah Tinggi Ilmu Kesehatan Holistik, 2018)
Background: Mouthwash on the market still contains a lot of ethanol which functions as an antiseptic, but ethanol in mouthwash can make the surface of the soft tissue of the mouth (mucosa) become dry and excessively spicy taste in mouthwash, so mouthwash that does not contain ethanol is even more popular. Objective: This study aims to make and test the stability of tea bags from saga leaves (Abrus precatorius Linn) and betel leaf (Piper betle) for mouthwash by organoleptic test for three weeks. Method: The research method used is action research with research instruments using observation sheets. The research was carried out by making simplicia from saga leaves and betel leaves and making preparations. The drying loss of saga leaves is 4.40% while betel leaves are 4.37%. The dosage formula is made based on a 50:50 comparison. The research was carried out by means of storage preparation of different temperatures at room temperature and cool temperatures. Stability testing by organoleptic observation, namely color, smell, taste and shape. Result: The results show that preparations stored at room temperature and cool temperatures are relatively stable, because they can last more than three weeks without any changes in color, taste and shape. The results of the room temperature storage obtained a distinctive smell of strong betel leaves, while at room temperature storage it was found that the characteristic odor of betel leaves was weak. Conclusion: Good stock stability is the preparation stored at cool temperatures, because the preparation does not experience significant changes in taste, color, smell, and dosage form.